Improving Knowledge and Self-Efficacy in Caring at Home for Parents with Low Birth Weight Babies - Sholihatul Amaliya; Rinik Eko Kapti; Asti Melani Astari; Laily Yuliatun; Nurona Azizah (Universitas Aisyah Pringsewu, 2023)
Low birth weight babies (LBWB) are more vulnerable to health problems. It is challenging to care them after discharge from the hospital. Mother knowledge and self-efficacy are essential components in determining the quality of care and health outcome of LBWB. However, research investigating mother’s self-efficacy (consisting of self-efficacy in general care, performing KMC, and giving breastfeeding) in parents of LBWB is rare. We aimed to determine the effect of an audiovisual-based educational package on knowledge and self-efficacy in caring for LBWB at home. The study was a pre-post quasi-experimental research with a control group of 48 postpartum mothers with LBWB who met the inclusion criteria. Twenty-four of these mothers whose babies were cared for in the perinatology unit were provided an audiovisual-based educational package as an intervention group, and the rest of these were provided health education standards from the hospital from August to November 2023. Data were collected using a maternal knowledge questionnaire and a modified perceived maternal parenting self-efficacy (PMP-SE) questionnaire. The data were analyzed using the Paired t-test/Wilcoxon and Kruskall-Wallis tests. The analysis revealed that comparison of increasing post-test mean scores across groups (control compared to intervention group) were significantly different in Mother's knowledge (p less than 0,007) and self-efficacy in providing care of LBWB (p less than 0,021; p less than 0,001 and p less than 0,001). The mother's knowledge and self-efficacy significantly improve after received an audiovisual-based educational package. An audiovisual-based educational package for mothers with LBWB can be a helpful nursing intervention to improve mothers' knowledge and self-efficacy. Abstrak: Bayi berat lahir rendah (BBLR) lebih rentan mengalami masalah kesehatan, sehingga perawatan BBLR di rumah menjadi hal yang sulit. Pengetahuan ibu dan efikasi diri merupakan komponen penting dalam menentukan kualitas asuhan dan status kesehatan BBLR. Namun penelitian yang mengidentifikasi efikasi diri ibu (yang terdiri dari efikasi diri dalam perawatan umum, melakukan KMC, dan memberikan ASI) pada orang tua dengan BBLR masih jarang. Peneliti bertujuan untuk mengetahui pengaruh paket edukasi berbasis audiovisual terhadap pengetahuan dan efikasi diri dalam merawat BBLR di rumah. Penelitian merupakan penelitian eksperimen semu pre-post dengan kelompok kontrol sebanyak 48 ibu nifas dengan BBLR yang memenuhi kriteria inklusi. Dua puluh empat ibu yang bayinya dirawat di unit perinatologi ini diberikan paket pendidikan berbasis audiovisual sebagai kelompok intervensi, dan sisanya diberikan pendidikan kesehatan standar dari rumah sakit. Penelitian dilakukan di rumah sakit pendidikan negeri di Jawa Timur dari Agustus hingga November 2023. Pengumpulan data dilakukan dengan menggunakan kuesioner pengetahuan ibu dan kuesioner perceived maternal parenting self-efficacy (PMP-SE). Data dianalisis dengan menggunakan Paired t-test/Wilcoxon dan Kruskall-Wallis. Hasil analisis menunjukkan bahwa perbandingan peningkatan skor rata-rata post-test antar kelompok (kontrol dibandingkan kelompok intervensi) berbeda bermakna, yaitu pada pengetahuan ibu nilai p kurang dari 0,007 dan efikasi diri dalam memberikan perawatan BBLR dengan nilai p kurang dari 0,021 (efikasi perawatan umum BBLR); p kurang dari 0,001 (efikasi PMK) dan p kurang dari 0,001 (efikasi menyusui). Pengetahuan dan efikasi diri ibu meningkat secara signifikan setelah mendapatkan pendidikan kesehatan menggunakan media audiovisual. Paket edukasi berbasis audiovisual untuk ibu dengan BBLR dapat menjadi intervensi keperawatan yang bermanfaat untuk meningkatkan pengetahuan dan efikasi diri ibu.